Ocular complications of severe vernal keratoconjunctivitis (VKC) in Yemen - Al-Akily, Saleh A.; Bamashmus, Mahfouth A. (Elsevier, 2011)
Objectives The objective of this study was to assess the ocular complications and visual loss among patients with severe vernal keratoconjunctivitis (VKC). Methods Four hundred and thirty-one patients with VKC seen at Ibn Al-Haitham Eye Center were the study group. This is a retrospective non-comparative observational study between 01 January 2002 and 31 December 2002. Visual acuity was measured with the standard Snellen visual acuity chart and for children under 5 years of age Kay pictures were used. Visual impairment was assessed by means of the World Health Organization criteria for visual disabilities. Cases with severe VKC that developed ocular complications leading to blindness and severe visual impairment were analyzed. Results The majority of VKC patients were males (75.9%) with a male:female ratio of 3.1:1. A total of 68 (15.7%) patients (54 boys and 14 girls) had severe VKC. The ocular findings among 20 patients with severe VKC that led to blindness and severe visual impairment included keratoconus (7); steroid-induced cataract (5), central corneal scars (5) and steroid-induced glaucoma (3). Two of the keratoconus cases developed acute hydrops. Conclusion Severe VKC in developing countries including Yemen is a potentially blinding disease. Visual loss may be due to keratoconus and corneal scars, as well as complications of the unsupervised use of topically administered corticosteroids.